Improvement of Concept Understanding Through the Development of Interactive Multimedia on Integer Operation Material - Griseldis, Mafaza Raissa; Khasanah, Laily Nurul; Septiani, Ni Luh; Prananto, Irfan Wahyu (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
Understanding the concept is the ability expected in every learning process. But not all students can master the understanding of the concept well. Researchers are trying to provide an alternative by creating interactive learning media to help understand mathematical concepts, especially integer material in grade 6 elementary schools. This research aims to develop a number-line interactive multimedia product to increase the understanding of the concept of addition of positive and negative integer operations. The purposes can be specified as follows: (1) to produce valid number-line interactive multimedia; (2) to produce number-line multimedia that is practical and effective; (3) to produce multimedia that can assist educators in the learning and teaching process. This research used the Research and Development (R&D) method with the ADDIE development model. This research was conducted in grade 6 of SD Negeri 1 Matenggeng. The targeted output of this research is to find out how to increase understanding of concepts through the development of interactive multimedia on positive and negative integer operations. The results obtained in this research were based on the validation of material experts, the results obtained were 4.41 very feasible classification. While the media validation shows a score of 4.25 with an interpretation of the very feasible classification. It can be concluded that this interactive learning media is feasible to use.Ade, S. M. (2018). Development of Interactive Multimedia-Based Learning Media.Ministry of Education and Culture. (2003). National Education System 20 of 2003.Ardianti, S. D., Christijanti, W., & Dewi, P. (2012). The Role of Animation Media with the Time Token Learning Method on Learning Activities and Results. Journal of Biology Education, 1(1)Ariani, N. & H. 2010. Multimedia Learning in Schools Guidelines for Inspirational, Constructive, and Prospective Learning. Jakarta: PT Prestasi Pustakarya.Ministry of National Education. 2003. Special Guidelines for the Development of a Junior High School Competency-Based Assessment System. Jakarta: Ministry of National Education.Dewi, A. P. (2021). Use of Interactive Slides in Online Learning Materials on Genetic Substances to Improve Students' Cognitive Aspects. WASIS: Scientific Journal of Education, 2(1), 55-61.Duffin, J.M.& Simpson, A.P. 2000. A Search for understanding. Journal of Mathematical Behavior. 18(4): 415-427.Erfan Priyambodo, A. W. (2012). The Effect of Web-Based Interactive Learning Media on Student Learning Motivation.Educational Journal, 99 - 109.Hanim, Fitria Amiruddin. (2016). Effect of Using Remote Sensing Interactive Learning Multimedia on Geography Learning Outcomes. Journal of Education, 1(4):Istiqlal, M. (2017). Development of interactive multimedia in learning mathematics.JIPMat, 2(1).Jannah, R., Ahmad, A., & Duskri, M. (2019). Understanding the Concept of Counting Integer Operations for Junior High School Students through Brain-Based Learning.Opportunity Journal, 7(2), 22-33.Kumalasani, M. P. (2018). The Practicality of Using Interactive Multimedia in Class IV SD Thematic Learning. Journal of Elementary Education, 2(1A), 1–11.Kurniawati, I.D. (2018). Interactive Multimedia-Based Learning Media to Improve Students' Understanding of Concepts.Journal of Computer and Information Technology, 68-75.Made Giri Pawana, N. S. (2014). Development of Project-Based Interactive Media with the ADDIE Model on Web Programming Material for Grade X Students of Even Semester at SMK N 3 Singaraja.e-Journal of Postgraduate Program at Ganesha University of Education, 1-10.Mayern, Richard E. 2009. Multi-Media Learning. Yogyakarta: Student Libraries.Mawaddah, S., & Maryanti, R. (2016). The ability to understand mathematical concepts of junior high school students in learning using the guided discovery model (discovery learning).EDU-MAT: Journal of Mathematics Education, 4(1).Muhsetyo, et al. 2007. Elementary Mathematics Learning. Jakarta: The Open University.Mulyono, B., & Hapizah, H. (2018). Understanding Concepts in Learning Mathematics.Kalamatica: Journal of Mathematics Education, 103-122.Novitasari, D. (2016). The influence of the use of interactive multimedia on the ability to understand students' mathematical concepts.FIBONACCI: Journal of Mathematics and Mathematics Education, 2(2), 8-18.Radiussman. (2020). Literacy Studies: Understanding Students' Concepts in Learning Mathematics.Journal of Mathematics and Mathematics Education, 1-8.Sanjaya, W. (2009). Classroom action research. Jakarta: Kencana Prenada Media Group. Sugiono. (2016). Quantitative Research Methods, Qualitative and R&D.Bandung: Alphabet.Sugiyono, P. (2016). Management Research Methods (Quantitative Approaches, Qualitative, Mixed Methods), Action Research (Action Research, and Evaluation Research).Bandung: Alfabeta Cv.Sukardjo. (2006). Collection of learning evaluation materials. Yogyakarta: Yogyakarta State University Postgraduate Program.Sukmadinata, Nana Syaodih. (2017).Educational Research Methods. Bandung: PT. Roesdakarya youth.Unaenah, E. (2020). Analysis of Students' Understanding in Counting Operations Adding Integers Using Number Lines.Journal of Education and Social Sciences, 296-310.Wahyuni, Esa. (2017). The Usage of Multimedia Improve Physics Learning Achievement. Journal of Prospective Learning. 2(2): 85- 86.Wahyuningtyas, D. T. (2015). Use of Toy Car Media to Increase Understanding of the Concept of Integer Count Operations.Journal of Educational Inspiration, 5(1), 587-592.Wahyuningtyas, D. T. & Iskandar, L. (2016) Improving Understanding of the Concept of Multiplication and Division of Integers Using Wayangmatika Media. Radiation Journal, 5(3): 51-60 Wahono, R. S. (2006). Aspects and criteria for evaluating learning media.Online)(http://romisatriawahono.net/, accessed on 15 March 2023).Widoyoko, E.P. (2012). Techniques for preparing research instruments.Yogyakarta: student library, 15(1), 1-22 Wildaniati, Y. (2016) Learning Integer Mathematics with Teaching Aids. Elementary Journal, 1(1): 33-40.